Concurrent Occurrence of Rectal Adenocarcinoma and Vulvar Keratinizing Squamous Cell Carcinoma: Case Report and Literature Review - Laukaitytė, Odeta; Brazytė, Gustė; Latkauskas, Tadas; Paškauskas, Saulius (Lietuvos chirurgija, 2025)
Introduction. Vulvar carcinoma is a rare malignancy, whereas rectal cancer is a more common oncological condition. However, the simultaneous occurrence of these two diseases is exceptionally rare. Case presentation. A 76-year-old woman presented with rectal bleeding and was previously diagnosed with keratinizing squamous cell carcinoma G1 of the vulva, unrelated to HPV. Imaging revealed tumor-like masses in the vulva and rectum, with pathological lymph nodes. Biopsy confirmed rectal adenocarcinoma in situ. She underwent obstructive rectal resection, colostomy formation, vulvar resection, and lymphadenectomy. Postoperative antibiotic therapy was administered and discontinued after seven days due to stable inflammatory markers. The patient was discharged in good condition, with planned rehabilitation in a sanatorium. Conclusion. Rectal adenocarcinoma and vulvar keratinizing squamous cell carcinoma concurrent occurrence is very rare. The risk factors for vulvar cancer (HPV, smoking, immunosuppression, lichen sclerosus) and rectal cancer (genetic predispositions, lifestyle factors (e.g., smoking, alcohol consumption), inflammatory bowel diseases) differ. However, genetic syndromes and certain interactions between lifestyle factors may lead to the concurrent occurrence of these two tumors. Given the complexity of managing two primary tumors, a multidisciplinary surgical approach was essential in our case. Further research is needed to explore possible biological links and optimize diagnostic and treatment strategies for such rare oncological presentations.
Keywords: rectal carcinoma; vulvar carcinoma; vulvar cancer risk factors; rectal cancer risk factors; vulvar squamous cell carcinoma and rectal adenocarcinoma